Persepsi Masyarakat Terhadap Kegiatan Penanaman Mangrove: Studi Kasus di Desa Sepatin Delta Mahakam - Tya Rahmasari Sulistianto; Oshlifin Rucmana Saud; Andi Nugroho; Achmad Syarifudin; Riza Fandi Ahmad; Nadya Ramadhani; Nazril Falah Yasir; Mega Putri Aulia Pabane; Juliyan Rahmat Fajar (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2025)
Public perception plays an important role in the success of mangrove planting activities. The community interacts directly with the mangrove ecosystem, so their perceptions will influence whether or not they will support and participate in planting activities. This study aims to determine the community's perceptions of mangrove planting activities in Sepatin Village, Mahakam Delta. The main data in this study were obtained through interviews. Interviews were conducted with 50 respondents who were selected purposively based on their involvement in mangrove planting activities. The research aspects consisted of four categories, namely knowledge, perception, participation, and future expectations. The data in this study were analyzed using descriptive statistics and presented in the form of diagrams and percentages. The results of the study show that 98% of respondents are aware of the mangrove planting activities carried out in Sepatin Village. The community has a very positive response to the planting activities, with 68% strongly agreeing and 32% agreeing with the activities. Mangrove planting activities have a positive impact on increasing fish catches and improving environmental quality. Several things need to be improved in mangrove planting activities, namely the need to involve the community in the planning and implementation of activities and to raise public awareness of the importance of mangrove ecosystems. Another thing that needs to be improved is the expectation that the government will provide adequate facilities and training for the community to support and enrich their knowledge on how to manage and utilize mangroves sustainably.